Desarrollo de un sistema automatizado para el lavado y refrigeración de un tanque de leche para la hacienda San Agustín - Brito Zapata, Adrian Marcelo (2017)
The present technical project was developed in the San Agustín farm, located in Aloag, in the area of milk storage, with the purpose of optimizing the washing and cooling processes in a milk tank, it allows to eliminate germs and save resources. To obtain this result the processes was automated by means of a PLC and HMI, it allow the control and supervision of the processes in the tank, such as: type of washing to be performed in the tank, level indicators, temperature and cooling control of milk, this represents an advantage over a manual washing, because the dosage of the chemical would be adequate, it allows to handle from a screen the configuration of the whole system for an automatic operation; the level and temperature sensors send its readings to the controller, it makes decisions to later run the cooling program and maintain the milk at a temperature between 2 and 4⁰C, the type of washing is selected from the HMI screen, this sends a selection data to a memory of the PLC, it chooses the type of washing and executes the process, according to the input of the configuration parameters that is made previously